2020
DOI: 10.3390/nano10071251
|View full text |Cite
|
Sign up to set email alerts
|

Single-Step Photochemical Formation of Near-Infrared-Absorbing Gold Nanomosaic within PNIPAm Microgels: Candidates for Photothermal Drug Delivery

Abstract: This work demonstrates the dynamic potential for tailoring the surface plasmon resonance (SPR), size, and shapes of gold nanoparticles (AuNPs) starting from an Au(I) precursor, chloro(dimethyl sulfide)gold (I) (Au(Me2S)Cl), in lieu of the conventional Au(III) precursor hydrogen tetrachloroaurate (III) hydrate (HAuCl4). Our approach presents a one-step method that permits regulation of an Au(I) precursor to form either visible-absorbing gold nanospheres or near-infrared-window (NIRW)-absorbing anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Marpu et al followed this work by developing a single-step method for synthesizing thermosensitive P(NIPAm-co-allylamine) microgels integrating AuNPs of various sizes, shapes, and plasmon resonance. [214] The hybrid microgels offer a tunable light-responsive platform for drug delivery via "squeeze out" mechanism.…”
Section: Sensingmentioning
confidence: 99%
“…Marpu et al followed this work by developing a single-step method for synthesizing thermosensitive P(NIPAm-co-allylamine) microgels integrating AuNPs of various sizes, shapes, and plasmon resonance. [214] The hybrid microgels offer a tunable light-responsive platform for drug delivery via "squeeze out" mechanism.…”
Section: Sensingmentioning
confidence: 99%
“…The in vitro results demonstrated that the combination of pulse wave laser illumination of nanorods could produce about a 93% reduction in cell viability, compared with control exposures. In studying drug delivery, Marpu et al proposed a one-step method for the photochemical formation of NIR-absorbing gold nanomosaic using thermoresponsive poly(N-isopropylacrylamide) microgels [ 9 ]. This nanomosaic was generated based on photochemical reduction of a gold precursor, without reducing agent or growth-assisting surfactants.…”
mentioning
confidence: 99%
“…As the application of polymer particles continues to expandalready including analytical, chromatographic, photonics, coatings, and biomedical applications the ability to control their synthesis and properties becomes increasingly valuable. It is often desirable to be able to tune the particle size, shape, composition, functionality, and porosity to suit the intended application. In particular, photochemistry has emerged as a heavily exploited tool in polymer and materials applications, including particle synthesis. Importantly, photochemistry enables finer control and milder conditions compared to traditional methods of particle synthesis, where elevated temperatures, radical reactions, extended reactions times, additives, and limited functionality are commonplace.…”
mentioning
confidence: 99%